الحركات المرورية ومحدداتها في التقاطع أسفل مجسر القيثارة في مدينة الناصرية (University of Thi-Qar Journal for Engineering Sciences, 2017)
The intersection is the most important part in the road system .The intersection may be at the same level which named " AT GRADE INTERSECTION" where all the vehicles are at the same level, or at different level which called "GRADE  SEPERATION" The choosed intersection "Al –Qithara Intersection" is one of the important intersections in the city therefore it was selected to evaluate traffic movements in this intersection. The filed measurements was conducted to collect the traffic data to find out the possible remedies to improve the traffic operation in the intersection. Two suggestions were submitted to improve the intersection performance. The first one depends on departure the traffic movements while the second suggestion includes the use of traffic signals. The main conclusion that in spite of the presence of al-Qithara Bridge the intersection is congested with many conflict points. The study recommended that the traffic movement should be modified and the intersection should be modified to signalized intersection.